The fourth ordeal: a history of the society of the Muslim Brothers in Egypt, 1973-2013 - Willi, V (2016)
This thesis is an internal organisational history of the Society of the Muslim Brothers in Egypt between 1973 and 2013. Based on memoires of Brotherhood leaders, as well as oral history interviews conducted in 2012 and 2013 with different rank-and-file members and dissidents, the thesis situates the life trajectories and personal experiences of these individuals within a larger national and international context. The purpose is to provide a historical account that is able to explain the reasons for the Brotherhood's cataclysmic failure of the summer of 2013. In accounting for the fall, my key argument centres on the internal rivalry between two political factions representing different "schools of thought", or visions, about the kind of organisation the Brotherhood was supposed to be. Representatives of the respective coalitions competed against each other over hegemony and organisational resources, basing their claims on contrasting intellectual traditions, political cultures and organisational values that had co-existed, sometimes uncomfortably, within the ranks of the Society since the times of Hasan al-Banna. The adherents of the "Qutbist" school of thought put forward the idea of a closed, pyramid-shaped and exclusive organisation, while those closer to 'Omar al-Tilmisani's model aspired to a reformed Society that was open to outsiders, and where internal progression was based on meritocracy, transparency and some form of democracy. I argue that it is through the holistic analysis of the complex dynamics between internal organisational politics, the use of ideology, and the personal experiences of key organisational members, that we are best able to grasp the Brotherhood's failed experience in governance in 2013.